2021
DOI: 10.3906/zoo-2012-23
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamics of small pelagic fish catches in the Marmara Sea in relation to changing environmental and bio-optical parameters

Abstract: The Marmara Sea has a large drainage basin that includes cities with heavy industrialisation and agricultural land use. Therefore, it is under the influence of significant anthropogenic activities that adversely affect the well-being of its ecosystem. The Marmara Sea is also an important fishing ground with many commercially important fish species. These fish species are also under the influence of the adverse impacts of anthropogenic activities. Fisheries catches in the Marmara Sea had experienced severe fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The low throughput cycled and FCI as well as a low overhead in the 2010s model suggested that ecosystem maturity, resilience and stability have been eroded over time (Finn, 1976;Ulanowicz, 1986). A considerable decrease in the grazing flows from TL I to TL II may indicate a decreasing carrying capacity of the ecosystem due to decreased primary productivity that was possibly related to the increasing sea surface temperatures (Akoglu, 2021). Further, the decreased energy transfers from detritus to TL II indicated a degradation in the ecosystem's maturity sensu Odum (1969), as in mature ecosystem there is greater cycling through detritus and the detrital compartments The keystoneness and the relative total impact of the functional groups in the SoM models.…”
Section: Ecosystem Structure and Functioning Within Decadesmentioning
confidence: 99%
“…The low throughput cycled and FCI as well as a low overhead in the 2010s model suggested that ecosystem maturity, resilience and stability have been eroded over time (Finn, 1976;Ulanowicz, 1986). A considerable decrease in the grazing flows from TL I to TL II may indicate a decreasing carrying capacity of the ecosystem due to decreased primary productivity that was possibly related to the increasing sea surface temperatures (Akoglu, 2021). Further, the decreased energy transfers from detritus to TL II indicated a degradation in the ecosystem's maturity sensu Odum (1969), as in mature ecosystem there is greater cycling through detritus and the detrital compartments The keystoneness and the relative total impact of the functional groups in the SoM models.…”
Section: Ecosystem Structure and Functioning Within Decadesmentioning
confidence: 99%
“…Due to global warming, the average seawater temperature has also been increasing. Therefore, as an ecosystem, there are many concurrent stressors currently being inflicted, which combined have also contributed to decreasing catches in addition to pressure from overfishing [26].…”
Section: Pressing Issues In the Marmara Seamentioning
confidence: 99%
“…The Marmara Sea is under the influence of significant anthropogenic activities that adversely affect the well-being of its ecosystem (Akoğlu, 2021). Fish species are also influenced by the adverse impacts of anthropogenic activities (Chassot et al, 2007).…”
Section: Implications For Whiting Fishery Managementmentioning
confidence: 99%